Choice of ATP Analogues for Biophysical Studies—A Systematic NMR-Based Investigation for the AAA Enzyme p97 - Maxim A. Droemer; Mikhail Shein; Anne K. Schütz (Biophysica)
ATP analogues are essential tools in enzymology and structural biology, but the structural and functional implications of their chemical modifications on nucleotide-binding proteins are often underappreciated. To address this, we evaluated a panel of ATP analogues, focusing on thiosubstituted and fluorinated molecules, using the AAA+ ATPase p97 as a benchmark system. Hydrolysis stability and impact on protein conformation, binding modes, and kinetics of enzymatic catalysis were assessed by protein-detected methyl NMR and ligand-detected 19F NMR in solution, as well as 31P solid-state NMR of nucleotides within protein sediments. ATPγS and AMP-PNP emerged as the most suitable analogues for preserving pre-hydrolysis states over extended periods, despite undergoing gradual hydrolysis. In contrast, both AMP-PCP and α/β-thiosubstituted analogues failed to induce native protein conformations in p97. Notably, we demonstrate a novel real-time NMR setup to explore the effect of nucleotide mixtures on cooperativity and the regulation of enzymes. Additionally, aromatic fluorine TROSY-based 19F NMR shows promise for direct ligand detection in solution, even in the context of large macromolecular complexes. These findings provide critical guidance for selecting ATP analogues in functional and structural studies of nucleotide-binding proteins.